2005
DOI: 10.1007/s10750-005-4447-0
|View full text |Cite
|
Sign up to set email alerts
|

An Under-appreciated Component of Biodiversity in Plankton Communities: The Role of Protozoa in Lake Michigan (A Case Study)

Abstract: Recent technological advances have led to the discovery that free-living, planktonic protozoa are ubiquitous in nature and appear to be important components of pelagic food webs (e.g., fluorescent straining, flow cytometry). Despite this, limited information exists tying their seasonality to rate processes that drive succession patterns. The abundance, and seasonal growth and grazing loss of an entire protozoan assemblage were evaluated in Lake Michigan. The protozoan assemblage was species-rich (100 taxa) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 99 publications
0
20
1
2
Order By: Relevance
“…However, the total number of species recorded in the present study (61 species) was higher than observed in other studies (Bossolan and Godinho, 2000;Wiackowski et al, 2001;Gomes and Godinho, 2003;Carrick, 2005;Cardoso, 2007), which registered between 17 and 36 ciliate species in plankton samples.…”
Section: Discussioncontrasting
confidence: 82%
“…However, the total number of species recorded in the present study (61 species) was higher than observed in other studies (Bossolan and Godinho, 2000;Wiackowski et al, 2001;Gomes and Godinho, 2003;Carrick, 2005;Cardoso, 2007), which registered between 17 and 36 ciliate species in plankton samples.…”
Section: Discussioncontrasting
confidence: 82%
“…Productivity in the Great Lakes is relatively low compared to the mesotrophic to eutrophic rivers, reservoirs, and backwater lakes where Asian carp commonly thrive. For example, phytoplankton biomass in Lake Michigan is typically \3 lg l -1 chlorophyll a (Carrick, 2005), whereas chlorophyll a values in the Middle Mississippi River can reach 40 lg l -1 (Williamson & Garvey, 2005). In order to predict if successful establishment of Asian carp in the Great Lakes is likely, it is necessary to determine how their feeding, growth, and survival is affected by a less productive environment.…”
Section: Introductionmentioning
confidence: 99%
“…Others have also suggested that a strong trophic link between mesozooplankton and microzooplankton exists within Lake Michigan. In particular, estimates of carbon flux from heterotrophic protozoans to mesozooplankton may rival that of phytoplankton to mesozooplankton (Carrick, 2005). Other studies using stable isotopes have also reported high trophic positions for previously described omnivore copepod species within African Lakes and have similarly suggested this may be the result of carnivory (Ngochera and Bootsma, 2010;Sarvala et al, 2003).…”
Section: Zooplankton Abundance and Biomassmentioning
confidence: 96%
“…Gardner (2004) demonstrated that bacteria can make up a significant portion of picoplankton in Lake Michigan. Likewise, average summer biomass of phototrophic protozoans can be as high as 50% of the average phytoplankton biomass within Lake Michigan (Carrick, 2005). Finally, differences in the location of various studies within the southern basin may also explain some of the observed discrepancies.…”
Section: Zooplankton Abundance and Biomassmentioning
confidence: 99%
See 1 more Smart Citation